Statement on the safety and efficacy of phosphoric acid 60% on silica carrier (UD60) for all animal species. (16th April 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The additive UD60 (phosphoric acid 60% on silica carrier) is intended to be used as a technological additive (functional group: preservative) for all animal species. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) assessed the data provided by the applicant in the technical dossier. During the course of the assessment, the need for additional information in order to be able to deliver an opinion on the safety and efficacy of this additive was identified and notified to the applicant. The information requested covered the characterisation, the safety for the target species and the efficacy of the additive. The applicant has failed to provide the additional information. Therefore, considering the data provided in the original dossier and the absence of response from the applicant to the requests from EFSA, the FEEDAP Panel is not in a position to deliver an opinion on the safety and efficacy of the additive UD60 (phosphoric acid 60% on silica carrier) as a technological additive for all animal species.